Pelaksanaan Pembelajaran Guru PJOK dalam Mengajar Siswa Berkebutuhan Khusus pada Masa Pandemi COVID-19 di SLB Kabupaten Wonosobo - Agung Wibowo; Cahyo Yuwono (Universitas Negeri Semarang, 2022)
The COVID-19 outbreak that hit Indonesia affected the education sector, including Special Schools. Online learning that is carried out for students with special needs makes teachers have to have creative ideas in the learning process. Therefore, the problem of this research is how implemetation is carried out by teachers in learning physical education for children with special needs during the pandemic at SLB Wonosobo Regency. The purpose of this study is to describe the implementation that teachers do in teaching students with special needs during the COVID-19 pandemic. This study uses a qualitative research method with a descriptive approach. The results of the research are creativity in the planning process carried out by physical education teachers by preparing syllabus, lesson plans, learning media and teaching materials, creativity in the learning process carried out by teachers by approaching students by prioritizing patience and compassion for students with special needs. , and creativity in the assessment system is carried out by looking at the level of student participation and the willingness to move in students. The conclusions is implementation of physical education teacher in accordance with learning situation during COVID – 19 pandemic.